Integrating Satellite-Tracking in Wildlife Conservation: A Review and Proposal - Strydom, Quintin Alan (Stellenbosch : Stellenbosch University, 2025)
Strydom, Q. A. 2025. Integrating Satellite-Tracking in Wildlife Conservation: A Review and Proposal. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/25244fab-a7ab-44b5-ae00-7c8a97af3c4f